Centered fan field region under wedge indentation by numerical solution method - Syafikah, Ayob; Nor Alisa, Mohd Damanhuri (The Mattingley Publishing Co., Inc., 2019)
A numerical solution method of stress distribution in the deformation region under wedge indentationare presented. The granular materials are assumed to obey Mohr-Coulomb yield condition in a plane strain condition. The numerical methods used to determine the stress field at each position (x,y) in the deforming region under the punch. The formation of the centered fan region was constructed by the network of the stress characteristic lines. The construction of the region is presented by using MATLAB. The solution obtained in this research only refer to the initial movement of the granular materials after the punch. The stress field obtained were then compared to the analytical solution. This solution method provides a simple algorithms that is easy to be applied in deformation and this will subsequently provide a contribution in designing tools and the construction industries involving granular materials.